2023
DOI: 10.5194/acp-2023-18
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physicochemical Characterization and Source Apportionment of Arctic Ice Nucleating Particles Observed in Ny-Ålesund in Autumn 2019

Abstract: Abstract. Ice nucleating particles (INPs) initiate primary ice formation in Arctic mixed-phase clouds, altering cloud radiative properties and modulating precipitation. For atmospheric INPs, the complexity of their spatiotemporal variations, heterogeneous sources and evolution via intricate atmospheric interactions challenge the understanding of their impact on microphysical processes in Arctic mixed-phase clouds and induce an uncertain representation in climate models. In this work, we performed a comprehensi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Figure 5a shows that the variability pattern of ABC WIBS resembles that of INPs and the both are signi cantly correlated, except ABC WIBS exhibits a fairly constantly lower concentration level by a factor of 5. This alone suggests that biological particles may constitute 20% of the INPs, which given their unique niche properties and observed concentration (i.e., nucleating ice at warmer temperatures than any other atmospheric INPs) 53 , means that they are an important driver of glaciation processes in clouds. The considerable contribution of biological particles to the observed INPs is also supported by Fig.…”
Section: Inp Diurnal Periodicity and Its Dependence On Aerosol Proper...mentioning
confidence: 99%
“…Figure 5a shows that the variability pattern of ABC WIBS resembles that of INPs and the both are signi cantly correlated, except ABC WIBS exhibits a fairly constantly lower concentration level by a factor of 5. This alone suggests that biological particles may constitute 20% of the INPs, which given their unique niche properties and observed concentration (i.e., nucleating ice at warmer temperatures than any other atmospheric INPs) 53 , means that they are an important driver of glaciation processes in clouds. The considerable contribution of biological particles to the observed INPs is also supported by Fig.…”
Section: Inp Diurnal Periodicity and Its Dependence On Aerosol Proper...mentioning
confidence: 99%
“…Data availability. The data presented in this study are available at https://doi.org/10.3929/ethz-b-000632439 (Li et al, 2023).…”
Section: Appendix B: Particle Size Distribution Of Case Studiesmentioning
confidence: 99%
“…However, cases with ice crystal number concentrations limited by the available INPs have also been observed in the Arctic (Pasquier et al, 2022b). Despite the extraordinary paucity of INPs in the troposphere and that at −15 • C, approximately 1 in 10 5 to 10 6 aerosol particles can act as an INP (e.g., Kanji et al, 2017;Petters and Wright, 2015); their type, abundance, and variability can indirectly affect the climate by altering the microphysical and radiative properties of MPCs (e.g., DeMott et al, 2010;Lohmann, 2002). For instance, cloud-resolving modeling studies revealed that the liquid and ice water path (Eirund et al, 2019), atmospheric stability (Jiang et al, 2000;Harrington et al, 1999), and precipitation (Harrington and Olsson, 2001) in the Arctic MPCs respond sensitively to INP perturbations in abundance and efficiency, and the responses were dominant over altering the cloud condensation nuclei (CCN) concentrations (Solomon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%